Application of deep convolutional neural network in multiclass skin cancer classification using custom CNN architecture - Shafique, Nadia; Shaheen, Kaynat Bint; Sikder, Zarjis Husain; Dey, Utsho; Swacha, Sharforaz Rahman (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.